Scientists, management and senior staff meeting with the DG - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
DG Sanginga in a town hall meeting with the Scientists, Management and Senior Staff on "Transforming IITA to a Project-based institution.